2018
DOI: 10.1111/clr.13352
|View full text |Cite
|
Sign up to set email alerts
|

Performance and outcome of zirconia dental implants in clinical studies: A meta‐analysis

Abstract: Objectives: To evaluate implant survival, peri-implant marginal bone loss, technical, and biological complications as well as aesthetic outcomes of zirconia implants in clinical studies. Material and Methods: Electronic (Medline, Embase) and hand searches were perinvestigating zirconia dental implants with a mean follow-up of at least 12 months. Primary outcomes were implant survival and peri-implant marginal bone loss. Secondary outcomes included technical and biological complications as well as aesthetic out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 91 publications
6
97
1
4
Order By: Relevance
“…There was a moderate consensus towards a tendency to ceramic materials coexisting with the standard titanium. Although the data from Zirconia‐based implants are scarce (Cionca, Hashim, & Mombelli, ; Pieralli, Kohal, Jung, Vach, & Spies, ; Roehling, Schlegel, Woelfler, & Gahlert, ), the “green” tendencies among populations from European Countries provide reasonable expectations for higher demands on non‐metal solutions. Similarly, although data on oral biofilm adherence to different implant surfaces are scarce, it is expected that ceramics may provide more cleansable surfaces (Sanz‐Martin, Sanz‐Sanchez, Carrillo de Albornoz, Figuero, & Sanz, ; Sanz‐Sanchez, Sanz‐Martin, Carrillo de Albornoz, Figuero, & Sanz, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a moderate consensus towards a tendency to ceramic materials coexisting with the standard titanium. Although the data from Zirconia‐based implants are scarce (Cionca, Hashim, & Mombelli, ; Pieralli, Kohal, Jung, Vach, & Spies, ; Roehling, Schlegel, Woelfler, & Gahlert, ), the “green” tendencies among populations from European Countries provide reasonable expectations for higher demands on non‐metal solutions. Similarly, although data on oral biofilm adherence to different implant surfaces are scarce, it is expected that ceramics may provide more cleansable surfaces (Sanz‐Martin, Sanz‐Sanchez, Carrillo de Albornoz, Figuero, & Sanz, ; Sanz‐Sanchez, Sanz‐Martin, Carrillo de Albornoz, Figuero, & Sanz, ).…”
Section: Discussionmentioning
confidence: 99%
“…There was a moderate consensus towards a tendency to ceramic materials coexisting with the standard titanium. Although the data from Zirconia-based implants are scarce (Cionca, Hashim, & Mombelli, 2017;Pieralli, Kohal, Jung, Vach, & Spies, 2017;Roehling, Schlegel, Woelfler, & Gahlert, 2018)…”
Section: Implant Designmentioning
confidence: 99%
“…However, only data from preclinical studies are included in the present review. The evaluation of the clinical data has been reported in a separate manuscript (Roehling, Schlegel, Woelfler & Gahlert, ). For the MEDLINE search, the following combinations of terms were applied:
“Dental implants” [MeSH] OR “dental implantation” [MeSH] AND “zirconium oxide” [MeSH] OR “yttria‐stabilized tetragonal zirconia” [MeSH] OR “zirconia” OR “zirconia implant*” OR “ceramic implant*” AND “osseointegration” [MeSH] or “bone‐implant‐interface” [MeSH] or “survival rate” [MeSH] or “success rate” or “marginal bone loss” or “soft tissue.”
…”
Section: Methodsmentioning
confidence: 99%
“…ROEHLING Et aL. in a separate manuscript (Roehling, Schlegel, Woelfler & Gahlert, 2018). For the MEDLINE search, the following combinations of terms were applied: "Dental implants" [MeSH] OR "dental implantation"…”
mentioning
confidence: 99%
“…Zirconia implants may well be advantageous in these situations thanks to their tooth‐like color (Elnayef et al, ; Ioannidis et al, ), and they offer the additional benefit of reduced bacterial and plaque adhesion (Cionca, Hashim, & Mombelli, ; Roehling et al, ). Anyway, their clinical use has rapidly increased in recent years due to the aforementioned growing demand for metal‐free alternatives to titanium implants, and numerous clinical and experimental studies have demonstrated excellent biocompatibility as well as promising short‐ and medium‐term outcomes (Haro Adanez, Nishihara, & Att, ; Piconi & Maccauro, ; Roehling, Schlegel, Woelfler, & Gahlert, ).…”
Section: Introductionmentioning
confidence: 99%